OP0031 Tocilizumab is Associated with Higher CDai/Sdai Remission in Biologic-Naïve Rheumatoid Arthritis Patients – Data from Reuma.Pt. (10th June 2014) - Romao, V.; Santos, M.; Polido-Pereira, J.; Duarte, C.; Nero, P.; Miguel, C.; Costa, J.; Pimentel-Santos, F.; Barcelos, F.; Costa, L.; Melo Gomes, J.; Pereira da Silva, J.; et al.
Abstract : Background: Tocilizumab (TCZ), an interleukin-6 receptor blocker, and anti-tumor necrosis factor (TNF) biologic agents are key therapies in the management of rheumatoid arthritis (RA). They are considered to be equally effective and very few head-to-head comparisons have been published. Objectives: To compare remission rates in RA patients treated with anti-TNF agents and TCZ and assess the impact of previous biologic therapies in treatment response. Methods: We included RA patients registered in the Rheumatic Diseases Portuguese Register, Reuma.pt, who started anti-TNF or TCZ after January 1, 2008, were treated for at least 6 months and had available DAS28 scores at baseline and at 6 months. Our primary outcome was the proportion of patients who achieved remission at 6 months by DAS28, CDAI, SDAI and Boolean remission criteria. Logistic regressions were performed to compare the groups and subgroup analyses of biologic-naïve patients were conducted. Results: 524 RA patients were enrolled, (106 adalimumab, 202 etanercept, 43 golimumab, 78 infliximab, 95 TCZ). At baseline, the groups were similar except for proportion of biologic-naïve patients (lower in TCZ group, p<0.0001) and mean DAS28, CDAI and swollen joint count, all higher in the TCZ group (respectively: p=0.0005, p=0.037 and p<0.0001). At 6 months, more TCZ-treated patients were in DAS28 remission, with no differences for CDAI, SDAI or Boolean remission. Considering only naïve patients, DAS28, CDAI and SDAI remission were significantly higher in the TCZ group compared to anti-TNF, with similar rates of Boolean remission. This was confirmed in the multivariate logistic regression, adjusting for age, gender, number of previous biologics and baseline disease activity: DAS28 OR 10.8 (5.9-19.7), CDAI OR 2.9 (1.3-6.5), SDAI OR 4.1 (1.8-9.5), Boolean OR 1.9 (0.88-4.3). Conclusions: TCZ treatment was associated with higher rate of DAS28 remission at 6 months and previous biologic therapy significantly affected CDAI/SDAI remission. Naïve patients treated with TCZ had better DAS28, CDAI and SDAI remission rates compared to those treated with TNF inhibitors, whereas the more stringent Boolean remission was similar among all groups. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2668